2017
DOI: 10.23937/2469-584x/1510053
|View full text |Cite
|
Sign up to set email alerts
|

Association of Helicobacter Pylori Infection and Diabetes Mellitus Type 2 Subjects in Yaounde Cameroon Using a Panel of Serum Biomarkers (PGII, HpIgG): A Case Control Study

Abstract: Introduction: Infection to Helicobacter pylori has been associated to many gastrointestinal diseases including gastritis, peptic ulcer disease, gastroesophageal reflux disease, atrophic gastritis and gastric cancer. Chronic infections are frequent and severe in patients with diabetes mellitus (DMT2), probably due to the impairment of their immune status. The link between H. pylori infection and diabetes mellitus (DM) remains controversial. This study aimed at detection and comparison of anti H. pylori antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 2 publications
5
5
1
Order By: Relevance
“…In another study done in Africa reported that 88% diabetic and 67% non-diabetic patients were found to have a positive status for anti-H. pylori antibodies. 17 Similar results were observed in a study by Jeon et al as well as Huang et al 18,19 On the other hand, some studies have found contradictory results. In diabetic group vs the non-diabetic group, H. pylori positive patients were 28.1% vs 29.6% in one study and 50.8% vs 56.4% in another study.…”
Section: Discussionsupporting
confidence: 78%
“…In another study done in Africa reported that 88% diabetic and 67% non-diabetic patients were found to have a positive status for anti-H. pylori antibodies. 17 Similar results were observed in a study by Jeon et al as well as Huang et al 18,19 On the other hand, some studies have found contradictory results. In diabetic group vs the non-diabetic group, H. pylori positive patients were 28.1% vs 29.6% in one study and 50.8% vs 56.4% in another study.…”
Section: Discussionsupporting
confidence: 78%
“…This is consistent with the previously reported studies. [ 4 5 6 7 8 9 10 16 17 18 19 20 21 ] Most recently, a meta-analysis suggested a trend toward more frequent H. pylori infections in T2DM patients. [ 3 ] Meanwhile, the impact of H. pylori and T2DM was explored in Bener et al .…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of studies has demonstrated that patients with DM are at a greater risk of HP infection [12][13][14][15][16], however the results certainly depend on the country where the research has been carried out and epidemiological situation with HP in the region. Some researchers have proved that HP infection is highly associated with T2DM, however its prevalence widely vary from 59% to 75% [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HP infection among patients with DM is debatable. However, some studies suggest the link between HP infection and T2DM, claiming that prevalence of HP among patients with T2DM is much higher than in non-diabetics [12][13][14] and patients with T1DM [15]. The group of Chinese researchers found opposite relationship: people with positive HP status are under the risk of DM [16].…”
Section: Introductionmentioning
confidence: 99%